The Collective Agency of Language Teachers under the Scheme of Research Excellence: Using a social network approach - Tao, Jian; Zhao, Ke; Chen, Xiuwen (Círculo de Lingüística Aplicada a la Comunicación, 2020)
This study adopted social network analysis (SNA) as a theoretical framework and methodological approach to understand the collective agency of a multilingual team of eight language teachers during their research practice in a Chinese university. As being guided by SNA that focuses on identifying social relationships and their impact, we used questionnaires and qualitative interviews to collect data and examine the emergence of collective agency. The data analysis revealed that the participants broke linguistic boundaries and engaged in cross-linguistic interactions. The findings further suggest that they offered complementary resources and emotional support for each other at individual, subgroup and group level. Based on the findings, this paper proposes a multi-layered understanding of collective agency to advance our knowledge of how to sustain collective agency. The findings point to the importance of addressing social interactions and relations in the emergence and enhancement of collective agency, so as to facilitate the professional development of language teachers.